Tongmenghui 同盟会 y Zhigongtang 致公党. El proyecto de República de Sun Yatsen y los chinos de ultramar (1894-1911) - Fierro de Jesús, Tonatiuh (2015)
This article analyzes the development of the Republic's project of Sun Yat-sen in overseas Chinese fraternal networks between 1894 and 1911. In this regard, two cases are analyzed: Tongmenghui同盟会 in Asia and Zhigongtang致公党 in the United States, Canada and some Latin American countries. These cases demonstrate the economic and political importance of overseas Chinese in the process of constructing Chinese nationalism and citizenship, as well as dynamism forged by the organization of overseas Chinese in defense of their own interests. Therefore, the aim of this study is to determine the extent of financial and political support, and the real possibilities that had Sun Yat-sen for the establishment of the Republic through the cooperation of fraternal associative networks.